The Proposal of a protocol of fertilization as a strategy for the control of nematodes in banana crop (Revista Científica Ciencias Naturales y Ambientales, 2018)
The cultivation of banana in Ecuador is vulnerable to the attack of pathogenic agents as nematodes, for this reason, it is here presented a protocol of fertilization generating abundant root mass as a strategy for the control of those. However, it is necessary to observe schemes of fertilization for banana established plantations with such problems. The methodology contrasts descriptive analysis and empirical bases established by banana farmers, analyzing macro and micro elements that interact in the nutrient solution of the soil, the unit of analysis with regards to elements and sources of fertilization, besides the qualitative effects that nematodes produce in plants. Therefore, yielding a protocol for banana fertilization focused on phosphorus as an addition to the nutritional requirement in established plantations to obtain good productivity. This protocol of fertilization will let the control of nematodes allowing a sustainable crop production.
Keywords: Nematodes; roots; fertilizatio; bananas